Does parental coaching affect children's false reports? Comparing verbal markers of deception. (19th February 2018) - Talwar, Victoria; Hubbard, Kyle; Saykaly, Christine; Lee, Kang; Lindsay, R.C.L.; Bala, Nicholas
Abstract : The present study examined differences in children's true and false narratives as a function of parental coaching by comparing the verbal markers associated with deception. Children ( N = 65, 4–7 years old) played the same game with an adult stranger over three consecutive days. Parents coached their children to falsely allege that they had played a second game and to generate details for the fabricated event. One week after the last play session, children were interviewed about their experiences. For children with the least amount of parental coaching, true and false reports could be distinguished by multiple verbal markers of deception (e.g., cognitive processes, temporal information, self‐references). The fabricated reports of children who spent more time being coaching by a parent resembled their truthful reports. These findings have implications for real‐world forensic contexts when children have been coached to make false allegations and fabricate information at the behest of a parent.